Video In Situ Snowfall Sensor (VISSS) data for Hyytiälä on 2022-05-13 - Maahn, Maximilian; Moisseev, Dmitri (In: Maahn, M; Moisseev, D (2023): Video In Situ Snowfall Sensor (VISSS) data for Hyytiälä (2021-2022) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.959046, 2023)
The VISSS is a camera system recording precipitating snowfall from two perspectives. Here, movies and images of falling precipitation particles are provided for one day at station Hyytiälä. For further details on the VISSS instrument see Maahn et al. (2023).